The mediating effect of technology innovation among export performance, firms’ heterogeneity and ESG performance - Luo, Xiao; Suwanna, Thanwarat; Nilapornkul, Napaporn (International Journal of Innovative Research and Scientific Studies, 2025)
This study aimed to explore the mechanisms and pathways through which firm heterogeneity, environment, society, and governance (ESG) performance, and technological innovation influenced firm exports. Based on panel data from China’s A-share main board listed companies between 2015 and 2022, the research empirically analyzed the impact of firm heterogeneity, ESG performance, and technological innovation on exports, while also examining the mediating role of technological innovation. The findings revealed that firm heterogeneity significantly affected exports, with ESG performance and technological innovation both having a positive influence on export performance. Furthermore, technological innovation partially mediated the relationship between ESG performance and exports. Additionally, group regression results on firm heterogeneity showed that the number of employees had a greater impact on exports than the total assets of the firm, suggesting that "human capital" played a more critical role in export performance than "total assets." As a result, enhancing ESG performance, increasing both assets and employee numbers, improving labor productivity, and advancing technological innovation were identified as key factors for boosting exports. Through the discussion of these findings, this study aims to offer insights for promoting sustainable economic development, informing government policies on low-carbon trade, and optimizing corporate production and operational strategies. It also seeks to enrich the existing theoretical framework, enhance the international competitiveness of companies in developing or emerging economies such as China, and provide new perspectives, ideas, and theoretical support for fostering the sustainable growth of the global economy.